2014
DOI: 10.1542/peds.2013-3903
|View full text |Cite
|
Sign up to set email alerts
|

Subdural Hemorrhage and Hypoxia in Infants With Congenital Heart Disease

Abstract: BACKGROUND AND OBJECTIVES: It has been suggested that there is a causal relationship between hypoxia and subdural hemorrhage (SDH) in infancy. The purpose of this study was to review the incidence of SDH in infants with congenital heart disease and explore the relationship between SDH and hypoxia. METHODS: Review of data collected for a prospective longitudinal cohort study of infants undergoing surgery for congenital heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…[113][114][115] Kelly et al 112 showed a similar proportion of neonatal SDH in infants with congenital heart disease, confirming the observation by pathologists that intradural and subdural bleeding is extremely common in neonates, even those who lack evidence of either trauma or overt hypoxia. [113][114][115] Kelly et al 112 showed a similar proportion of neonatal SDH in infants with congenital heart disease, confirming the observation by pathologists that intradural and subdural bleeding is extremely common in neonates, even those who lack evidence of either trauma or overt hypoxia.…”
Section: Prolonged Hypoxia and Advanced Resuscitationsupporting
confidence: 52%
“…[113][114][115] Kelly et al 112 showed a similar proportion of neonatal SDH in infants with congenital heart disease, confirming the observation by pathologists that intradural and subdural bleeding is extremely common in neonates, even those who lack evidence of either trauma or overt hypoxia. [113][114][115] Kelly et al 112 showed a similar proportion of neonatal SDH in infants with congenital heart disease, confirming the observation by pathologists that intradural and subdural bleeding is extremely common in neonates, even those who lack evidence of either trauma or overt hypoxia.…”
Section: Prolonged Hypoxia and Advanced Resuscitationsupporting
confidence: 52%
“…In recent years, however, the certainty with which it can be determined that the findings of the triad are in fact attributable to traumatic shaking has been questioned (18)(19)(20)(21)(22)(23)(24)(25)(26). Many articles which have debated the subject of traumatic shaking and the symptoms and signs of the triad have been published in international and national journals and in the media.…”
Section: Presenting Medical Historymentioning
confidence: 99%
“…COMMENTARY. In patients suspected of having a hereditary metabolic cause for infantile spasms, the authors recommend a more liberal application of advanced diagnostic techniques, such as whole exome sequencing, muscle biopsy for mitochondria biochemical and genetic studies, and newer neuroimaging techniques such as 3 Tesla MRI and PET scanning [1]. More extensive genetic testing is justified in higher risk populations where high consanguinity rates are prevalent.…”
Section: Neurometabolic Causes Of Infantile Spasmsmentioning
confidence: 99%
“…The report addresses the advances in diagnosis and treatment of children with intellectual disabilities since the original AAP report in 2006 [1]. Intellectual disability (ID) is characterized by significant limitations both in intellectual functioning and in adaptive behavior as expressed in conceptual, social and practical adaptive skills.…”
Section: Developmental Disorders Aap Genetics Diagnostic Approach To mentioning
confidence: 99%